Review of different Structural irregularities in buildings - Varadharajan, S.; Sehgal, V.K.; Saini, Babita (Journal of Structural Engineering, 2024)
The present study summarizes the research works done in the past regarding different types of structural irregularities i.e. Plan and vertical irregularities. Criteria and limits specified for these irregularities as defined by different codes of practice (IS1893:2002, EC8:2004 etc.) have been discussed briefly. It was observed that the limits of both Plan and vertical irregularities prescribed by these codes were comparable. Different types of modeling approaches used have also been discussed briefly. The review of previous research works regarding different types of plan irregularities justified the preference of multistorey building models over single storey building models and concept of balanced CV (Center of strength) – CR (Center of rigidity) location was found to be useful in controlling the seismic response parameters. Regarding the vertical irregularities it was found that strength irregularity had the maximum impact and mass irregularity had the minimum impact on seismic response. Regarding the analysis method MPA (Modal pushover analysis) method even after much improvement was found to be less accurate as compared to dynamic analysis.